Percobaan Ekonomi untuk Mengkaji Pengaruh Informasi serta Jumlah Penjual dan Pembeli dalam Transaksi Pasar - Supriyadi, Edy (Journal the Winners: Economics, Business, Management, and Information System Journal, 2010)
Perfect competition (PPS) is the most ideal market structure because this market system is considered will ensure the realization of activities producing goods and services with very high efficiency compared to other market structures such as monopoly. Due to its benefits for sellers and buyers, economists often wish for the creation of perfect competition. In the pattern of transactions in everyday life, there are many market transactions commonly encountered, such as decentralized systems (DT), and Double Auction (DA). This paper presents the use of experimental methods to study the characteristics of both systems the transaction is in a "perfect competitionâ€ (5 sellers and 5 buyers' and market monopoly (with 1 seller and 5 buyers). Responses observed are Contract Price (CP), market efficiency, CP diversity coefficient on the price balance, buyer surplus and seller surplus. From the experimental results can be seen that the average Contract Price (CP) during 5 experimental periods that the value of CP at Perfect Competition Market is smaller than the monopoly market. From efficiency levels between transactions type it can be seen that the Double Auction type of transaction is more efficient than with the Decentralization type of transaction.